An investigation on cutting of the cold work steel X153CrMoV12 by WEDM. Issue 10 (9th September 2021) - Ceritbinmez, Ferhat
Abstract : Purpose: Wire electric discharge machining (WEDM) is a non-conventional machining process, which is used for cutting parts of civil and military aircraft, rotorcraft, satellites and spacecraft. The cold work steel X153CrMoV12 is used in molds that are needed to produce plastic and metal parts used in these areas. It is only possible to produce parts with precise dimensions and quality with the use of mold steels with sensitive surfaces. The purpose of this study is to analyze X153CrMoV12 material by cutting it with WEDM method in precise dimensions. Design/methodology/approach: The effects of varying cutting parameters on the size of the finished product, surface roughness (SR) and surface hardness were determined by making rough in one pass and precision cuts in different passes. Nikon SMZ745T, Mitutoyo micrometer, Mitutoyo SJ-210 and Insize ISHL-P100 were used for macro-analysis, dimensional control, SR and surface hardness, respectively, to determine the cut qualities. Findings: According to the hardness measurement results obtained from the steel surface before cutting and from the cut surfaces after cutting, there was no significant change in the surface hardness owing to the use of heat-treated steel. Increasing the wire tension as a result of the increase in the number of cutting passes and the decrease in the amount of rough stock left for the final cut increased the cut quality. Cutting precision has increased by preventing vibration of the wire with zero upper and lower water pressure required for slag cleaning. Originality/value: There are many studies on WEDM in the literature, but there is no similar study emphasizing the importance of the processing parameters such as the number of cutting passes and rough stock amount. In this study, cold work steel with a hardness of 56–60 HRC was machined as rough cut in one pass, rough and fine cut in double pass, double fine cut after one roughing in three passes. As a result of the cuts, 3 µm measurement precision and 0.998 Ra SR were obtained as well as there was no hardness change in the cut surfaces.